Endothelial Palmitoylation Cycling Coordinates Vessel Remodeling in Peripheral Artery Disease. Issue 2 (3rd July 2020) - Wei, Xiaochao; Adak, Sangeeta; Zayed, Mohamed; Yin, Li; Feng, Chu; Speck, Sarah L.; Kathayat, Rahul S.; Zhang, Qiang; Dickinson, Bryan C.; Semenkovich, Clay F.
Abstract : Rationale: Peripheral artery disease, common in metabolic syndrome and diabetes mellitus, responds poorly to medical interventions and is characterized by chronic vessel immaturity leading to lower extremity amputations. Objective: To define the role of reversible palmitoylation at the endothelium in the maintenance of vascular maturity. Methods and Results: Endothelial knockout of the depalmitoylation enzyme APT-1 (acyl-protein thioesterase 1) in mice impaired recovery from chronic hindlimb ischemia, a model of peripheral artery disease. Endothelial APT-1 deficiency decreased fibronectin processing, disrupted adherens junctions, and inhibited in vitro lumen formation. In an unbiased palmitoylation proteomic screen of endothelial cells from genetically modified mice, R-Ras, known to promote vessel maturation, was preferentially affected by APT-1 deficiency. R-Ras was validated as an APT-1 substrate, and click chemistry analyses demonstrated increased R-Ras palmitoylation in cells with APT-1 deficiency. APT-1 enzyme activity was decreased in endothelial cells from db/db mice. Hyperglycemia decreased APT-1 activity in human umbilical vein endothelial cells, due, in part, to altered acetylation of the APT-1 protein. Click chemistry analyses demonstrated increased R-Ras palmitoylation in the setting of hyperglycemia. Altered R-Ras trafficking, increased R-Ras palmitoylation, and fibronectin retention were found in diabetes mellitus models. Loss of R-Ras depalmitoylation caused by APT-1 deficiency constrained R-Ras membrane trafficking, as shown by total internal reflection fluorescence imaging. To rescue cellular phenotypes, we generated an R-Ras molecule with an inserted hydrophilic domain to circumvent membrane rigidity caused by defective palmitoylation turnover. This modification corrected R-Ras membrane trafficking, restored fibronectin processing, increased adherens junctions, and rescued defective lumen formation induced by APT-1 deficiency. Conclusions: These results suggest that endothelial depalmitoylation is regulated by the metabolic milieu and controls plasma membrane partitioning to maintain vascular homeostasis. Abstract : Supplemental Digital Content is available in the text.